3D mapping Helsinki: How mega digital models can help city planners. Issue 4 (2nd October 2017) - Cousins, Stephen
Abstract : Helsinki has developed two massive city-wide 3D models to help streamline urban planning and development, improve energy consumption and boost citizen engagement. To model the city, 50, 000 oblique photographs were taken and the resulting 11-terabyte dataset was processed using a variety of software applications and a farm of 10 computers. Twelve pilot projects will exploit the models, including one to calculate the solar-power generating potential of around 80, 000 buildings. Here, the city's project manager in charge of the initiative explains how it will work, and the challenges they face.